A Waking Review: Old and Novel Insights into the Spore Germination in Streptomyces - Bobek, Jan; Šmídová, Klára; Čihák, Matouš (Frontiers in Microbiology, 2017)
The complex development undergone by Streptomyces encompasses transitions from vegetative mycelial forms to reproductive aerial hyphae that differentiate into chains of single-celled spores. Whereas their mycelial life – connected with spore formation and antibiotic production – is deeply investigated, spore germination as the counterpoint in their life cycle has received much less attention. Still, germination represents a system of transformation from metabolic zero point to a new living lap. There are several aspects of germination that may attract our attention: 1. Dormant spores are strikingly well prepared for the future metabolic restart; they possess stable transcriptome, hydrolytic enzymes, chaperones, and other required macromolecules stabilized in a trehalose milieu; 2. Germination itself is a specific sequence of events leading to a complete morphological remodeling that include spore swelling, cell wall reconstruction, and eventually germ tube emergences; 3. Still not fully unveiled are the strategies that enable the process, including a single cell’s signal transduction and gene expression control, as well as intercellular communication and the probability of germination across the whole population. This review summarizes our current knowledge about the germination process in Streptomyces, while focusing on the aforementioned points.